THE IMPACT OF SOCIAL CHANGE ON THE IMPLEMENTATION OF LAW POLICIES IN SOCIETY - Anessa Permata Zahra (Academic Solution Publisher, 2025)
This study discusses the relationship between law and society, as well as how law functions as a tool to regulate and balance social behavior. The main focus of the research is to understand how law adapts to social changes influenced by cultural values, customs, religion, and norms. Using literature study and qualitative data analysis methods, the research examines the application of law in various regions with different social backgrounds. The results of the study show that law plays a significant role as a social control mechanism, a driver of change, a symbol of communication, and an integrator in maintaining societal harmony. This study also highlights the importance of the restorative justice approach in resolving conflicts peacefully and effectively. Through this principle, law not only functions as an enforcer of rules but also as a means of strengthening social relationships and building solidarity. Furthermore, public legal awareness is identified as a key factor in creating compliance with applicable rules. Therefore, the main recommendation of this research is the development of a legal system that is more responsive and flexible to social dynamics in order to address the challenges of globalization. With the implementation of adaptive and inclusive law, it is hoped that order, justice, and harmony will be achieved in community life